The impact of stock market capitalisation, international investment, clean energy on CO2 emissions: New insight from listed domestic companies in Belgium - Benjamin Ampomah Asiedu; Emmanuel Adu Boahen (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
The paper fundamentally explores the impact of Belgium's stock market capitalization, international investment, clean energy on CO2 emissions from 1990-to 2018. More pertinently, our study analogizes the diverse impact of Belgium's stock market capitalization, international investment, clean energy, and environmental quality. Through cointegration analysis, stock market capitalization, international investment, clean energy, and environmental quality have long-run links. Granger causality test indicates that International investment has a unidirectional relationship with environmental quality; clean energy has a bi-directional relationship with environmental quality. Via the static and dynamic regression, we found that stock market development has the most significant impact on carbon dioxide emissions in static and dynamic regression. Renewable energy has a positive impact on the carbon dioxide emissions per static, and dynamic regression and economic growth harm environmental quality in Belgium. The impulse response function results show that the Stock market and international investment positively respond to environmental quality. Our empirical findings provide policies to advocate improving environmental quality in Belgium.